2018
DOI: 10.1186/s12913-018-3147-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a direct-to-consumer information campaign on prescription patterns for overactive bladder

Abstract: BackgroundDirect-to-consumer information (DTCI) campaign is a new medium to inform and empower patients in their decision-making without directly promoting specific drugs. However, little is known about the impact of DTCI campaigns, expanding rapidly in developed countries, on changes in prescription patterns. We sought to determine whether a DTCI campaign on overactive bladder increases the prescription rate for overactive bladder treatment drugs.MethodsWe performed a 3-year retrospective cohort study of 1332… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In these models, the time since start of study was entered as a continuous variable indicating the month since start whereas intervention periods is a dummy variable indicating pre-intervention "0", otherwise "1" [20,22]. These analysis were performed in STATA version 16 [23].…”
Section: Quantitative Analysis Of Secondary Datamentioning
confidence: 99%
“…In these models, the time since start of study was entered as a continuous variable indicating the month since start whereas intervention periods is a dummy variable indicating pre-intervention "0", otherwise "1" [20,22]. These analysis were performed in STATA version 16 [23].…”
Section: Quantitative Analysis Of Secondary Datamentioning
confidence: 99%
“…The number of DA campaigns has grown rapidly in the US, 15 as well as in countries where DTCA is forbidden. 16–18 DA campaigns are part of companies’ strategies to encourage patients to seek help for medical conditions for which prescription drugs are available. 5 There is evidence that patient requests for medication subsequent to DA campaigns may influence doctors’ prescription behavior and this raises concerns that warrant ethical recommendations.…”
Section: Benefits and Risksmentioning
confidence: 99%
“…Arguments made in favor of DA campaigns include the promotion of patient autonomy and improved public health thanks to increased diagnosis, better management and treatment of rare, serious or debilitating diseases, as well as de-stigmatization of diseases (e.g., HIV) or embarrassing symptoms (e.g., erectile dysfunction). 15 , 16 , 20–22 The Israeli Ministry of Health established regulations regarding DA campaigns to specifically empower consumers by providing them with information about the availability of treatments for diseases (medications or preventive treatments) in a manner that does not involve the promotion of a particular commercial product. 21 …”
Section: Benefits and Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wallington et al (2018) showed that the introduction of a mass media campaign was associated with increased consumer information search, displayed by high click-through rates to a website and more referrals to medical centers. Relatedly, Zaitsu et al (2018) found that patients were more likely to obtain a first prescription of a treatment following a direct-to-consumer advertising campaign designed to educate them and provide resources about health-related decisions. The positive impact of advertising initiatives by firms may even spill over to the category level, as Wosińska (2005) noted that advertising by a brand increased consumer drug therapy compliance of its rival brands’ products.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%